Site-specific fertilization approach increased productivity of rainfed ‘Ataúlfo’ mango - Salazar-García, Samuel; Ibarra-Estrada, Martha Elva; Hernández-Valdés, Edgardo Federico; Medina-Torres, Raúl; Fregoso-Tirado, Luis Enrique (REVISTA TERRA LATINOAMERICANA, 2019)
There is considerable diversity in fertilization management of ‘Ataúlfo’ mango (Mangifera indica L.) in the state of Nayarit, Mexico, and there is no systematic information available in this regard. The aim of this research was to evaluate the medium-term effect (2010‑14) of the site-specif ic fertilization approach on fruit yield and size in ‘Ataúlfo’ mango grown under rainfed conditions (annual average summer rainfall 1300-1450 mm). Two commercial orchards at 8 × 8 m spacing, one each in San Blas and Compostela municipalities in Nayarit were chosen. Fertilization treatments were: 1) Normal dose, which considered tree nutrient demand, periods of maximum root growth, nutrients provided by the soil, leaf nutrient concentrations and fertilization eff iciency; 2) High dose (1.5 times the normal dose); 3) Control, annual application of 3 kg per tree of 17-17-17 (N, P2O5, K2O). Soil and leaf samples were taken for nutrient analysis throughout the study. Treatments were randomly applied to 20 single tree-replicates at each orchard. For cumulative yield and fruit size a 2 × 3 factorial arrangement (orchards × treatments) was used. For leaf nutrient concentrations, the year and fertilization treatments effect was analyzed using 10 replicates per treatment. Means comparison was performed with the Waller-Duncan test (P ≤ 0.05). The Normal dose increased yield 38% as compared to the Control, as well as fruit size. The highest total fruit yield and C22 (196-220 g) and C20 (221-250 g), as well as the highest cost-benef it, were obtained with the Normal dose. This treatment consisted of applying per year and tree, depending on the orchard, 509-608 g N, 21-206 g P, 132-582 g K, 19-234 g Mg, 6.5-18 g Fe, 6-46 g Mn, 2-6 g Zn and 3-13 g B.